Evaluation and Strategic Recommendations for BRIN's RIIM Start-up Program - Adara Permata Halimatunnisa (Journal Integration of Management Studies, 2025)
The study aims to analyze the effectiveness of the National Research and Innovation Agency (BRIN) 's Research and Innovation for Indonesia Advanced (RIIM) program in promoting research commercialization, thereby bridging scientific research to the market through start-up incubation. This study employs a qualitative research approach through in-depth interviews with BRIN policymakers, qualitative questionnaires administered to 11 start-up graduates of the RIIM program, and secondary data analysis of participants' final reports. The analysis utilizes the TOWS matrix to develop strategic recommendations and the TOPSIS analysis to prioritize these strategies. The RIIM program yielded mixed results, with a technological readiness level (TRL) of 7.1/9 and a business readiness level (BRL) of 6.1/10. However, there are critical gaps in manufacturing readiness (MRL 5.9/10) and commercial readiness (CRL 5.6/9), indicating the 'valley of death'. Key limitations include inadequate physical infrastructure, mentors who prioritize administration over strategy, suboptimal post-incubation monitoring, inflexible funding structures, and limited networks with investors. This study provides empirical evidence on the effectiveness of government research commercialization programs in developing countries. Using TOPSIS analysis on the strategies derived from the TOWS matrix, five priority recommendations emerge: building incubation infrastructure through external partnerships, optimizing internal research teams, facilitating collaborative projects between researchers and start-ups, leveraging innovation focus to achieve competitive advantage, and establishing a comprehensive post-incubation monitoring system. This study presents new empirical evidence on the effectiveness of BRIN's RIIM program and gives recommendations that can scale up similar innovation programs, create jobs, strengthen national competitiveness, and address social challenges through local economic and technological development.